PD-0200347, an α2δ ligand of the voltage gated calcium channel, inhibits in vivo activation of the Erk1/2 pathway in osteoarthritic chondrocytes: a PKCα dependent effect. Issue 5 (25th October 2005) - Boileau, C; Martel-Pelletier, J; Brunet, J; Schrier, D; Flory, C; Boily, M; Pelletier, J-P
Abstract : Objective: To explore the in vivo effects of PD-0200347, an α2 δ ligand of voltage gated Ca 2+ channels, on cell signalling in osteoarthritic (OA) chondrocytes from an experimental dog model, and examine the effect of PD-0200347 on the major signalling pathways involved in OA cartilage degradation. Methods: OA was surgically induced in dogs by sectioning the anterior cruciate ligament. OA dogs were divided into three groups and treated orally with ( a ) placebo; ( b ) 15 mg/kg/day PD-0200347, or ( c ) 90 mg/kg/day PD-0200347. The animals were killed 12 weeks after surgery. Cartilage specimens from femoral condyles and tibial plateaus were processed for immunohistochemistry. Specific antibodies against the phosphorylated form of PKCα, Ras, c-Raf, the MAP kinases Erk1/2, p38, JNK, and the transcription factors, CREB and Elk-1, were used. Results: Levels of all the tested signalling mediators were increased in the placebo treated (OA) group compared with the normal group. PD-0200347 treatment significantly reduced the levels of the active forms of PKCα, c-Raf, Erk1/2, and Elk-1; however, the levels of the active forms of Ras, p38, JNK, and CREB were not affected by the PD-0200347 treatment. Conclusion: The action of PD-0200347 on OA chondrocytes is probably mediated through the inhibition of Erk1/2 activation via a Ras independent mechanism. This effect is associated with reduction of the activation of transcription factors such as Elk-1, which leads to the inhibition of the induction of the major catabolic factors involved in the degradation process of OA cartilage.